Pharmacokinetics and pharmacodynamics of oral P2Y12 inhibitors during the acute phase of a myocardial infarction: A systematic review. Issue 143 (July 2016) - Khan, Nazish; Cox, Anthony R.; Cotton, James M.
Abstract: Background: The immediate administration of oral antiplatelet therapy in the form of aspirin plus a P2Y12 inhibitor is the universally recognised standard of care for patients who present with acute myocardial infarction. Despite strong recommendations for their use, there are a paucity of data describing their onset of action and clinical efficacy during the short time frames from confirmation of diagnosis to reperfusion with primary percutaneous coronary intervention. Objectives: To complete a systematic review evaluating the currently available evidence regarding the pharmacokinetic and pharmacodynamic activity of orally administered clopidogrel, prasugrel and ticagrelor during the acute phase of a myocardial infarction in relation to mechanical reperfusion with primary percutaneous coronary angioplasty. Methods: We searched PubMed and EMBASE databases up to January 2016 using the terms outlined in our search strategy. Results: Twelve papers were included in our final analysis; seven relating to pharmacodynamic studies, one to a pharmacokinetic study and four to pharmacokinetic/pharmacodynamic studies. Conclusion: Our results indicate that despite the administration of oral P2Y12 inhibitors including newer more potent agents that should allow for greater and more consistent levels of platelet inhibition, the physiological state of ST segment elevation MI (STEMI) and the co-administration of opioid based analgesia are associated with a reduction in the degree of platelet inhibition achieved following their administration.